(untitled) (Revista INFAD de Psicología. International Journal of Developmental and Educational Psychology., 2014)
The theme of Entrepreneurial Education has acquired more and more importance in the last years as, in the present economic situation, there is a growth of the exigency, above all among young people, to reinvent themselves and to create their own personal business. This happens in every field of the labor market, even in the fashion world. The present research has, in fact, the goal to introduce a real course on entrepreneurial education inside fashion agencies, to offer young models the basics to become entrepreneurs and make the most of their skills and attitudes, to make their way in a world which, contrary to what it seems, is not only made of beauty. The sample is represented by a group of eighty five (85) models who are part of different fashion agencies. The focus of this study is represented by the subject and his intraentrepreneurial being inside the work context.